Results Following Operative Treatment of Tibial Plateau Fractures - Urruela, Adriana M.; Davidovitch, Roy; Karia, Raj; Khurana, Sonya; Egol, Kenneth A. (The Journal of Knee Surgery, 2013)
A total of 96 displaced tibial plateau fractures in 94 patients (average age, 48 years) were treated with open reduction and internal fixation. At 12 months postoperatively, mean range of knee motion was 126 degrees and 10 (10%) of the patients had required a secondary surgery. Using a binary regression model, no demographic variable such as age, gender, smoking history, diabetes, BMI; or fracture characteristic such as mechanism of injury, initial plateau depression, Schatzker classification was identified that correlated with short-term functional outcome such as a complication, range of motion, healing time, or residual depression. We determined that radiographic fracture reduction was not superior following fractures with less initial displacement, and increased plateau collapse at 12 months postoperatively was not indicative of decreased function. However, an increased postoperative articular step-off was found to be associated with an increased risk of plateau collapse (p < 0.01). Furthermore, at 12 months, 76% of the patients had returned to their preinjury employment and the overall complication rate was 13%.
Keywords: tibial plateau; fracture; ORIF; Schatzker; outcome